Epithelial and muscle progenitor cells in peripheral blood in duchenne muscular dystrophy - Marwa Mohammed Yahia Qwema; Hala Hamdi Shaaban; Iman Ahmed Ehsan Abdelmeguid; Soheir Saad Korraa (Cairo : Marwa Mohammed Yahia Qwema, 2010)
The most common lethal myopathic disease is DMD , which is an x- liked recessive disease that affects 1: 3500 males . Here we assassed whether the levels of certain stem cells may predict the progression of duchenne muscular dystrophy DMD
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Duchenne dystrophy; Muscular; Stem cell